NOTEWORTHY. - Merz, Terri; A. L. (Humanities)
News briefs are provided as of July 2014 related to the U.S. National Endowment for the Humanities (NEH). The NEH has moved to a new location in Washington, D.C. The 1984 film "Solomon Northup's Odyssey," directed by Gordon Parks, was shown May 20, 2014 at the U.S. National Archives in Washington, D.C. A location-based game is being created by a team led by Miami University theater professor Ann Elizabeth Armstrong that will highlight the role played by Western College in 1964's Freedom Summer.